Robert Kagan, un « néo-conservateur » emblématique - Pierre Guerlain (Revue LISA)
This article is an analysis of the new rhetoric of imperialism developed by Robert Kagan and the wrongly named "neo-conservatives" who have shaped the foreign policy of the Bush Administration. Kagan resorts to a gendered view of international relations which idealizes the use of force and reinvigorates the concepts and mental categories of Theodore Roosevelt. Kagan’s dismissal of and scorn for the Europeans critical of the Bush Administration take a pseudo philosophical form but boil down to shopworn biological conceptions. Rather than being typical of American views of Europe, Kagan’s neo-imperialist musings are those of a clearly identified ideological group that now exerts enormous influence over the White House, and are strongly opposed by other Americans.